Pengaruh Model Games Based Learning Berbantuan Alat Peraga Jerapah Tompina terhadap Minat Belajar Siswa Kelas III Sekolah Dasar - Anzilni Auliya Akifa; Anni Malihatul Hawa (Journal on Education, 2024)
This research aims to determine the differences between the GBL learning model assisted by tompina giraffe props on learning interest and also to determine the effect of using the GBL learning model assisted by tompina giraffe props on the learning interest of class III students at Cahaya Ummat Elementary School. The subjects in this research were students in classes III A and III B at SDIT Cahaya Ummat. The type of data in this research is quantitative using quaci experimental design in the form of nonequivalent control group design. Data collection techniques in this research used tests (pretest and posttest) and non-tests (observation, interviews and documentation). The data analysis techniques in this research are normality test, homogeneity test, hypothesis test in the form of independent sample t-test and simple linear regression test. The results of the research show that: (1) There is a difference in the use of the GBL model assisted by tompina giraffe props on student learning interest. This can be proven by the results of the Independent Sample T-Test with a value of less than 0.05, namely 0.003 < 0.05. So it can be concluded that there is a significant difference between the experimental class and the control class, where the experimental class has an average of 77% greater than the average of the control class, namely 66%. (2) There is an influence of using the GBL model assisted by tompina giraffe props on students' learning interest. This can be proven from the results of the Simple Linear Regression Test with a sig value of less than 0.05, namely 0.000 < 0.05. So, regarding the learning interest variable, it can be concluded that there is an influence of the GBL model assisted by tompina giraffe props on students' learning interest of (R Square value 0.722 or 72.2%).